Numerical Study on Effect of High-rise Building on Wind and Thermal Environments in Idealized Urban Array: Impacts of Planar Density - P. Ding; X. Zhou (Journal of Applied Fluid Mechanics, 2023)
How the high-rise (HR) building affects the pedestrian-level wind environment (PLWE) is of great significance to urban planning. Therefore, the effects of the HR building on the wind and the thermal environments in the urban array with different planar densities are studied numerically. The planar densities are 0.25, 0.4 and 0.6. The simulation results reveal that the HR building can strongly affect the flow dynamics and the heat transfer mechanisms in the urban array. Compared with the low-rise (LR) buildings, the presence of the HR building in the surrounding buildings creates high-speed downwash airflow in the upstream street, and the velocity of downwash airflow increases with the increase of planar density. The turbulent kinetic energy at pedestrian level around the HR building increases. When the planar density is large, the direction of the wake airflow behind the HR building is alternating. And long periods of high-speed airflow are observed, which do not occur in the wake of the target LR building. The temperature around the HR building is lower than that around the target LR building. The surface heat flux around the HR building is greater than that around the target LR building. The surface heat flux around the HR building increases with the increase of the planar density, which is contrary to that around the target LR building.